The ICC and Central Europe: Why we should care? - Hassanova, Rebecca Lilla (The ICC at 25: Lessons Learnt, 2025)
The following article explores the implications of the ICC and its Rome Statute on Central Europe, focusing particularly on Hungary, the Slovak Republic, the Czech Republic, and Germany. It examines the integration of the Rome Statute into national legal systems, highlighting both the operational challenges faced during its implementation and the varying degrees of compliance among the examined countries. Through a detailed analysis of Hungary's complex implementation issues, the Slovak Republic's smoother ratification process, the Czech Republic's legislative hesitations, and Germany's proactive approach, the study illustrates the multifaceted relationship between international and domestic law concerning international criminal justice. Central themes include the principle of complementarity, the treatment of high-ranking officials' immunity, and the successful incorporation of core international crimes into national legislation.Keywords: Rome Statute, International Criminal Court, implementation, legislation, international criminal law